2011
DOI: 10.1007/s00266-011-9677-0
|View full text |Cite
|
Sign up to set email alerts
|

Nipple Reconstruction Using a Star Flap Enhanced by Scar Tissue: The Regina Elena Cancer Institute Experience

Abstract: We maintain that the technique presented here is safe, easy to perform, and reproducible and improves the long-term projection of the reconstructed nipple.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Nipple reconstruction was performed for 4 patients using our previously described technique [ 18 ] followed by tattooing the areola, for 4 patients using a tissue graft from the genitalia, and for 3 patients using a star flap.…”
Section: Resultsmentioning
confidence: 99%
“…Nipple reconstruction was performed for 4 patients using our previously described technique [ 18 ] followed by tattooing the areola, for 4 patients using a tissue graft from the genitalia, and for 3 patients using a star flap.…”
Section: Resultsmentioning
confidence: 99%
“…3,4,16–19 Goh et al 20 was one of the few studies evaluating different NAC flap techniques and found equivocal levels of satisfaction between reconstruction techniques. Gullo et al 21 provided evidence that the star flap achieves good overall patient satisfaction among patients undergoing breast reconstruction. Jabor et al 22 evaluated numerous types of flaps (star, nipple sharing, keyhole, skate, S) and found equivocal satisfaction between techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, the choice results in the sacrifice of creating an additional scar to achieve optimal nipple position, thus abandoning the use of previous scars. The use of avascular scar tissue as a free graft harvested from a linear fragment of mastectomy scar, in combination with the healthy skin of a local flap, has been already proposed [10]. Nevertheless, the use of an adjacent mastectomy preexisting scar as donor-site for flaps harvesting has been avoided for many years due to the fear of flap ischemia and necrosis [11,12].…”
Section: Discussionmentioning
confidence: 99%